Economic and non-economic factors on gross domestic product growth that impacts income Distribution in Indonesia - Tri Widiarto; Cicih Ratnasih; Meirinaldi Meirinaldi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2026)
This study aims to examine and analyse the effects of economic and non-economic factors on Gross Domestic Product (GDP) growth and their implications for income distribution in Indonesia. Economic factors are represented by household consumption, domestic investment, foreign investment, government expenditure, and loans, while the non-economic factor is represented by the Indonesian Democracy Index. This research employs a quantitative approach using panel data. The data consist of secondary data covering 33 provinces in Indonesia (cross-section) over an annual period (time series) from 2014 to 2023. The data were collected through documentation and library research, utilizing official publications from government institutions and relevant scientific literature. The analytical tool used in this study is EViews version 13. The results indicate that household consumption, domestic investment, foreign investment, government expenditure, loans, and the Indonesian Democracy Index have both simultaneous and partial effects on GDP growth in Indonesia. Furthermore, GDP growth is proven to have a significant effect on income distribution in Indonesia, with a strong explanatory power of the model. Among the explanatory variables, government expenditure has the largest coefficient (β = 0.373430) and is statistically significant (p-value = 0.0430 < 0.05), indicating that government expenditure is the most dominant factor in driving GDP growth.